Pengaruh Debt To Equity Ratio (DER) Dan Debt To Total Asset Ratio (DAR) Terhadap Profitability Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2014-2017 - Yolandafitri Zulvia (Economac: Jurnal Ilmiah Ilmu Ekonomi, 2019)
This study aims to look at the relationship between Debt to Equity Ratio and Debt to Total Asset Ratio to profitability in manufacturing companies listed on the Stock Exchange in the 2014-2017 period. The population in this study were all Manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2017 period of 156 companies. The sampling technique uses purposive sampling so that the manufacturing companies that are sampled are 97 companies. Data analysis used multiple linear regression which began with the classic assumption test which consisted of a normality test, an autocorrelation test, a heterokedasticity test and a multicollinearity test. Hypothesis testing using the F test and t test. The results showed that the variable Debt to Equity Ratio (DER) and Debt to Total Asset Ratio (DAR) had a significant effect with a significance level of 0.00 meaning <of 0.05 on Return on Assets (ROA)